In silico characterization of defensin in Musa acuminata DH Pahang (MaDef) provides insight into potential defence-related protein - Abd Rahman, Muhammad Syahmi; Zixin, Hong; Baharum, Nadiya Akmal (The Malaysian Society for Biochemistry and Molecular Biology (MSBMB), 2023)
Plant defensins are expressed in response to phytopathogens and various defencerelated signalling molecules. They possess diverse biological properties such as antifungal, antibacterial and proteinase inhibitory, as well as playing roles in plant growth and development. Multiple defensin copies are identified in numerous plant species, such as Arabidopsis, Brassica oleracea, Zea mays and Medicago truncatula. To our knowledge, the multigene family of defensin has never been reported in bananas. In addition, specific banana defensin genes involved in the defence and stress responsiveness are yet to be identified. Thus, this study predicts specific copies of Musa acuminata DH Pahang (wild banana) defensins that are potentially involved with defence and biotic stress response using in silico analysis. A total of 6 defensin copies from Musa acuminata DH Pahang (wild banana) (MaDef) were identified and categorised under the Knottin₁ clan (CL0054). All of them except Ma07t03680.1 carry conserved sequences of the gamma-thionin domain (PF00304). A total of 8 cysteines forming 4 disulfide bridges are found across all six MaDef peptide sequences. Using phylogenetic analysis, wild banana defensins are categorised under three clades with the predicted molecular weight of 8 to 9 kDa. Gene ontology (GO) revealed that all MaDefs except for Ma07t03680.1 are involved in defence response. Furthermore, analysis of the promoter regions through PlantCARE shows Ma04t36140.1 is associated with defence and stress responsiveness. Overall, this study contributes to a deeper understanding of defensins characteristics and functional predictions, which are critical for future crop advances against biotic challenges, notably in bananas.